Frustration-driven C 4 symmetric order in a naturally-heterostructured superconductor Sr2VO3FeAs - Jong Mok Ok (Nature Portfolio, 2017)
Iron-based superconductors exhibit complex couplings between different electronic degrees of freedom, leading to unusual correlated phases. Ok et al. show that Sr2VO3FeAs develops a hidden order state due to frustrated interactions between the magnetic fluctuations of its SrVO3 and SrFeAs layers.